«VERBAL ASPECT AS A DRIVING FORCE OF PLOT DEVELOPMENT AND CHARACTER PORTRAYAL IN GOGOL’S POEM «DEAD SOULS» - M. S. Shodieva,Z. P. Farmonova (International Journal of Literature and Language Studies, 2026)
This study examines the role of verbal aspect in Nikolai Gogol’s poem Dead Souls. The analysis demonstrates that the opposition between perfective and imperfective verb forms serves as an important stylistic device for developing the plot and portraying characters. Perfective verbs convey completed actions, narrative dynamics, and the progression of events, whereas imperfective verbs reveal the characters’ inner world, behavioral traits, and habitual actions. Through the system of verbal forms, the author creates vivid portraits of landowners, officials, and the protagonist, Pavel Chichikov. The study concludes that verbal aspect performs not only a grammatical but also a significant artistic function, helping to express the author’s intentions and the ideological content of the work.